The Legal Protection on Consumers of E-Commerce Transactions in Indonesia - Daud, Edward Zeth; Suyanto, Heru (Law Development Journal, 2024)
As time progresses, people's lives are starting to be influenced by developments in information technology, including in the field of trade, where buying and selling transactions that can be carried out using the internet are known as electronic commerce or e-commerce for short. However, in its implementation it is necessary to pay attention to consumer protection. The method that will be used in this research is an empirical normative legal approach. The results of this research show that the form of legal protection for consumers in e-commerce transactions has been regulated based on the provisions of statutory regulations which have been contained in Law No. 8 of 1999 concerning Consumer Protection (UUPK), then in purchasing and selling transactions, although carried out online, based on the ITE Law and PP PSTE, it is still recognized as an electronic transaction that can be accounted for through an electronic contract. Legal protection for consumers due to default in electronic transactions is by providing compensation, compensation, and/or services received or utilized that are not in accordance with the agreement. Based on regulations regarding the responsibility of business actors, the actions of business actors must refer to the principles of responsibility in law.